2018
DOI: 10.1002/iub.1757
|View full text |Cite
|
Sign up to set email alerts
|

Orexins Facilitates Osteogenic Differentiation of MC3T3‐E1 Cells

Abstract: Dysfunction of osteoblastic bone formation and matrix mineralization plays a key role in the pathological development of osteoporosis. The orexin peptide orexin-A, a highly excitatory neuropeptide hormone, possesses various biological functions by activating its specific G protein-coupled receptors, orexin-1 receptor (OX1R) and orexin-2 receptor (OX2R). Here, we report that OX1R but not OX2R was expressed in MC3T3-E1 cells. Importantly, we found that orexin-A accelerated osteoblast differentiation and matrix m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(34 reference statements)
2
9
0
Order By: Relevance
“…For example, Orexin-A-induced osteoblastic formation and matrix mineralization and the activation of the PKD/p38 MAPK pathway are mediated by OXR1. 32 Orexin-A could stimulate the expression of GLUT4 in a glucose-dependent manner in primary hepatocytes via Erk1/2, JNK, and p38 signaling. 33 In addition, Dandan’s studies have shown that Orexin-A exerted its neuroprotective effects in vivo and in vitro by suppressing over-activated autophagy by modulating the OXR1-mediated MAPK/Erk/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Orexin-A-induced osteoblastic formation and matrix mineralization and the activation of the PKD/p38 MAPK pathway are mediated by OXR1. 32 Orexin-A could stimulate the expression of GLUT4 in a glucose-dependent manner in primary hepatocytes via Erk1/2, JNK, and p38 signaling. 33 In addition, Dandan’s studies have shown that Orexin-A exerted its neuroprotective effects in vivo and in vitro by suppressing over-activated autophagy by modulating the OXR1-mediated MAPK/Erk/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Bone metabolic balance depends on the interaction of bone formation and bone resorption, indicating the disorder is caused by an imbalance between osteoblasts and osteoclasts (15,16), which is also the key cause of PMO. Osteoblasts play a vital role in bone formation and are controlled by several signaling pathways, including PI3K/P38/AKT pathways (17)(18)(19). This study aimed to evaluate the osteoprotective effects of dioscin on PMO rats and explore dioscin's mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Orexin-A peptide and OX1R specific inhibitor SB334867 (MCE, China) were stored in α-MEM. 3T3 cells were stimulated with OM in the presence or absence of orexin-A (5µM) and SB334867 (10 nM) 13 for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…Upon orexin binding to OX1R or OX2R, orphan G protein-coupled receptors, it regulates sleep-wake states, feeding behaviors and energy homeostasis. 11 , 12 Furthermore, it is reported that orexin-A can accelerate osteoblast differentiation and matrix mineralization in the murine osteoblastic cell-line MC3T3-E1 cells in vitro 13 and orexin knockout mice display a lower-bone-mass phenotype. 14 Previous studies have suggested that orexin-A expression affects the occurrence of airway diseases, such as OSA, chronic obstructive pulmonary disease, and narcolepsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation